2020
DOI: 10.1155/2020/8140989
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA AFAP1-AS1 Promotes Cell Proliferation and Metastasis via the miR-155-5p/FGF7 Axis and Predicts Poor Prognosis in Gastric Cancer

Abstract: Background. Actin filament-associated protein 1-antisense RNA 1 (AFAP1-AS1) plays an important role in the development and progression of several human cancers. However, its biological function in gastric cancer (GC) progression is still unknown. Methods. We used qRT-PCR to detect the relative expression of AFAP1-AS1 in GC tissues and cell lines. The loss-of-function assays were conducted to detect the effect of AFAP1-AS1 on GC development. Bioinformatics analysis, luciferase reporter gene analysis, and RIP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Zhu et al reported that FGF7 could promote breast cancer progression through AKT signaling pathway [ 39 ]. In GC, several studies indicated that FGF7 might play a role in GC cell proliferation and metastasis [ 40 , 41 ]. The product of gene NPR3 encodes one of the natriuretic peptide receptors and responsible of clearing natriuretic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al reported that FGF7 could promote breast cancer progression through AKT signaling pathway [ 39 ]. In GC, several studies indicated that FGF7 might play a role in GC cell proliferation and metastasis [ 40 , 41 ]. The product of gene NPR3 encodes one of the natriuretic peptide receptors and responsible of clearing natriuretic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…It is the subcellular localization of NATs that are closely related to their different mechanisms of biological functions ( Bergalet et al, 2020 ). Normally, nuclear NATs are mainly involved in transcriptional interference, epigenetic modifications, RNA pocessing and alternative splicing, whereas cytoplasmic NATs are mainly involved in RNA stability and/or mRNA translatability ( Xu et al, 2019 ; Ma et al, 2020 ; Xu et al, 2020 ). Therefore we examined the subcellular localization and the protein coding potential of Nqo1-AS1.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 In addition, work in GC cells has indicated that lncRNA AFAP1-AS1 promotes proliferation and metastasis via miR-155-5p/FGF7 regulatory axis. 37 In this study, Linc-ROR was negatively correlated with miR-212-3p, while Linc-ROR was positively correlated with FGF7 expression in gastric tissues. Further, the dual-luciferase reporter assay confirmed that the direct interaction between Linc-ROR and miR-212-3p, miR-212-3p and FGF7 3ʹUTR mRNA.…”
Section: Discussionmentioning
confidence: 46%